An Examination of Dawud (David A.S) Fasting For Women and its Effectiveness from Physio-Psychological Perspective - sholikhah, Qurrotul Ainin; Aliyah, Himatul (Journal Intellectual Sufism Research (JISR), 2020)
Abstract. This research was conducted to determine the urgency of Dawud fasting for women from a physio-psychological perspective. This research is a type of qualitative descriptive research, by making direct observations or observations. The target of this study is to determine the urgency of Dawud fasting in women from the perspective of physio-psychology and Sufism for students of the Jagad Alimussirry Islamic boarding school. The data collection technique was carried out by means of interview and literature review. Meanwhile, for data analysis, the researcher used an interactive model from Miles and Huberman and to test the validity of the data,the researcher used Triangulation technique. The results obtained that the habit of Dawud Sunnah fasting for women could make them accustomed to be able to introspect (muhasabah) their own mistakes, be patient and sincere, motivate oneself to think positively and optimistically, be empathetic towards others and adapt well to the environment. Dawud fasting is very important and suitable for the fair sex. By not leaving Lillahita'ala's intention to worship, it will automatically train a variety of things that can guide a women in facing every problems in their life as well as making a women special not only physically but also psychologically and spiritually.